2018
DOI: 10.1177/1753466618816625
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of autologous blood versus talc pleurodesis for malignant pleural effusion: a randomized controlled trial

Abstract: Background:Autologous blood is a novel, high-efficacy sclerosant for treatment of malignant pleural effusion (MPE), similar to tetracycline. There has been no comparative data between autologous blood and a worldwide sclerosant like talc. We aimed to compare the effectiveness of autologous blood versus talc pleurodesis.Methods:A prospective study was conducted at Songklanagarind Hospital, Songkhla, Thailand. A total of 123 symptomatic MPE cases were randomized to receive autologous blood pleurodesis (ABP) vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In a prospective study of 56 patients with malignant pleural effusion, Keeratichananont et al compared autologous pleurodesis and talcum powder, and demonstrated that they had an equivalent efficacy. Moreover, they reported that recipients of AB had significantly lower fever, pain score and length of hospital stay [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 56 patients with malignant pleural effusion, Keeratichananont et al compared autologous pleurodesis and talcum powder, and demonstrated that they had an equivalent efficacy. Moreover, they reported that recipients of AB had significantly lower fever, pain score and length of hospital stay [36].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcomes were treatment success, treatment failure, and survival. We integrated previous criteria [28][29][30][31][32][33] as follows: (1) complete response (CR) is a pleural effusion disappeared for more than four weeks, or the lack of accumulation of uid; (2) partial response (PR) is a pleural effusion was reduced more than 50% for more than four weeks or a 50% decrease in the effusion; (3) no response (NR) or stable disease (SD) is pleural effusion was reduced less than 50% or increased less than 25% or the effusion recurred but required no further therapy; (4) progressive disease (PD) is pleural effusion increased more than 25% along with other signs of progressive disease or symptomatic re-accumulation of the effusion requiring repeat thoracentesis or chest tube. We de ned the treatment success as CR plus PR, and treatment failure as NR/SD plus PD.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Treatment lasting one to eight times, mainly three to four times, it still did so (Table.3 h, Fig.S36 and 38). The evaluation criteria were Millar and Ostrowskimj [28][29][30][31][32][33]. The TPs with platinum achieved the above effects using the two criteria (Table.3i, Fig.S40 and 42).…”
Section: Subgroups and Meta-regression Analysismentioning
confidence: 99%
“…32 Furthermore, the use of silver nitrate instillation as a "rescue" after failed talc poudrage showed 89% efficacy; although 1,000 mg was used, minimal side effects were noted. 33 Table 1 Agents used for pleurodesis [14][15][16][17][18][19]27,28,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] When evaluating the safety profile, there was equal success when using doses of 90, 150, and 180 mg with dose-dependent increases in systemic inflammatory responses, suggesting the lower dose is preferable. 34 However, pain control was a significant concern, 35 resulting in the decline in its use.…”
Section: Silver Nitratementioning
confidence: 99%
“…The benefits of ABP by administering approximately 100 to 150 mL of autologous blood introduced via a chest tube in both studies were the significantly lower rates of pain and fever and lower hospital LOS. 51,52 Larger studies are required to confirm the findings of these smaller studies and could offer a more cost-effective alternative with minimal side effects. ABP use in pneumothoraces also appears to be promising.…”
Section: Other Agentsmentioning
confidence: 99%